Impact of COVID-19 Outbreak on Women Quality of Life in Indonesia - Sufyan, Dian Luthfiana; Syah, Muhammad Nur Hasan; Nurbaya, Nurbaya (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The COVID-19 outbreak and its designated policy conveyed unprecedented impacts on the life of women. This study aims to assess women’s quality of life (QOL) during the pandemic. This cross-sectional study was conducted in Java and Sulawesi, as both sites implemented the large-scale social restriction policy. The Indonesian version of the WHO Quality of Life Instrument, Short Form (WHOQOL-BREF) was used to collect the QOL data. The whole questionnaire was self-administered online by 191 women using Google Form. Descriptive analysis and Mann-Whitney test were carried out to analyze the data in statistical software. Overall, women who were involved in this study conveyed a relatively moderate quality of life (4.08 + 0.76 SD). The highest and lowest mean scores of QOL were observed in the social relationship (78.3 + 17.05 SD) and physical health domain (60.8 + 10.76SD). Family monthly income and type of family were significantly associated with environmental health (p0.05). Astoundingly, during the outbreak women described high satisfaction on social relationship. These results may advocate policy in regards to women’s welfare.